Association of Smoking Status With Angina and Health-Related Quality of Life After Acute Myocardial Infarction. (September 2015) - Buchanan, Donna M.; Arnold, Suzanne V.; Gosch, Kensey L.; Jones, Philip G.; Longmore, Lance S.; Spertus, John A.; Cresci, Sharon
<x xml:space="preserve">Abstract</x> Background— Smoking cessation after acute myocardial infarction (AMI) decreases the risk of recurrent AMI and mortality by 30% to 50%, but many patients continue to smoke. The association of smoking with angina and health-related quality of life (HRQOL) after AMI is unclear. Methods and Results— Patients in 2 US multicenter AMI registries (n=4003) were assessed for smoking and HRQOL at admission and 1, 6, and 12 months after AMI. Angina and HRQOL were measured with the Seattle Angina Questionnaire and Short Form-12 Physical and Mental Component Scales. At admission, 29% never had smoked, 34% were former smokers (quit before AMI), and 37% were active smokers, of whom 46% quit by 1 year (recent quitters). In hierarchical, multivariable, regression models that adjusted for sociodemographic, clinical and treatment factors, never and former smokers had similar and the best HRQOL in all domains. Recent quitters had intermediate HRQOL levels, with angina and Short Form-12 Mental Component Scale scores similar to never smokers. Persistent smokers had worse HRQOL in all domains compared with never smokers and worse Short Form-12 Mental Component Scale scores than recent quitters. Conclusions— Smoking after AMI is associated with more angina and worse HRQOL in all domains, whereas smokers who quit after AMI have similar angina levels and mental health as never smokers. These observations may help encourage patients to stop smoking after AMI.